RELATIONSHIP BETWEEN FLORAL MORPHOLOGY, FRUIT SETTING BEHAVIOR AND FINAL YIELD IN SOME EGGPLANT (Solanum melongena) GENOTYPES FROM IRAN - Khaleghi,Sedighehsadat (Universidad de Concepción. Facultad de Agronomía, Facultad de Ingeniería Agricola y Facultad de Ciencias Veterinarias, 2021)
ABSTRACT Heterostyly in eggplant flowers is a common trait that may affect the fruit production. The objective of this study was to evaluate the impact of heterostyly on fruit setting and yield of 13 eggplant genotypes from Iran. Flowers capable of setting fruit, including long- (LGs) and medium-styled flowers (MEs), accounted for the largest number of flowers (43.60-75.62%), while total short-styled flowers (SRTs) constituted a smaller percentage (20.47-45.51%) in different genotypes. However, SRTs represented a considerable proportion of the total number of eggplant flowers. Different eggplant genotypes produced 42.59-77.25% fruits from LGs+MEs, and only 0.0-3.77% from SRTs. In general, although the percentage of fruit setting of LGs and MEs was much greater compared to values of SRTs, there was no significant correlation between final yield and style length. Therefore, in order to increase eggplant yield, protecting fruits formed from LGs and MEs might be more effective than increasing the proportion of LGs and MEs to SRTs.